Impaired Gastric Gland Differentiation in Peutz-Jeghers Syndrome - Udd, Lina (American Society for Investigative Pathology, 2010)
Gastrointestinal hamartomatous polyps in the Peutz-Jeghers cancer predisposition syndrome and its mouse model (Lkb1(+/−)) are presumed to contain all cell types native to the site of their occurrence. This study aimed to explore the pathogenesis of Peutz-Jeghers syndrome polyposis by characterizing cell types and differentiation of the epithelium of gastric polyps and predisposed mucosa. Both antral and fundic polyps were characterized by a deficit of pepsinogen C-expressing differentiated gland cells (antral gland, mucopeptic, and chief cells); in large fundic polyps, parietal cells were also absent. Gland cell loss was associated with an increase in precursor neck cells, an expansion of the proliferative zone, and an increase in smooth muscle α-actin expressing myofibroblasts in the polyp stroma. Lack of pepsinogen C-positive gland cells identified incipient polyps, and even the unaffected mucosa of young predisposed mice displayed an increase in pepsinogen C negative glands (25%; P = 0045). In addition, in small intestinal polyps, gland cell differentiation was defective, with the absence of Paneth cells. There were no signs of metaplastic differentiation in any of the tissues studied, and both the gastric and small intestinal defects were seen in Lkb1(+/−) mice, as well as polyps from patients with Peutz-Jeghers syndrome. These results identify impaired epithelial differentiation as the earliest pathological sign likely to contribute to tumorigenesis in individuals with inherited Lkb1 mutations.